2018
DOI: 10.14569/ijacsa.2018.090518
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Prediction using Data Mining Techniques: A Systematic Literature Review

Abstract: Abstract-Rainfall prediction is one of the challenging tasks in weather forecasting. Accurate and timely rainfall prediction can be very helpful to take effective security measures in advance regarding: ongoing construction projects, transportation activities, agricultural tasks, flight operations and flood situation, etc. Data mining techniques can effectively predict the rainfall by extracting the hidden patterns among available features of past weather data. This research contributes by providing a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 26 publications
0
19
0
2
Order By: Relevance
“…Many researchers have used machine learning techniques to resolve the classification problems in various areas including: sentiment analysis [11,12,13,14,15,16], network intrusion detection [17] "in press" [18], [19], rainfall prediction [20,21], and software defect prediction [10], [29] etc.. Some selected studies regarding the software defect predictions are discussed here briefly.…”
Section: Related Workmentioning
confidence: 99%
“…Many researchers have used machine learning techniques to resolve the classification problems in various areas including: sentiment analysis [11,12,13,14,15,16], network intrusion detection [17] "in press" [18], [19], rainfall prediction [20,21], and software defect prediction [10], [29] etc.. Some selected studies regarding the software defect predictions are discussed here briefly.…”
Section: Related Workmentioning
confidence: 99%
“…It helps in ongoing constructions, flight operations, transportation etc. Aftab [1] et al have made a study on different articles published during 2011 and 2017 and made a comparison on the different data mining techniques to be used as the base line for the early prediction of rainfall. Data mining techniques can be a better tool than the traditional methods for predicting the rainfall at an early stage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The final result showed that 1000 epochs giving minimum error rate when compared to 500 and 1500 epochs [15]. Shabib Aftab, Munir Ahmad, Noureen Hameed, Muhammad Salman Bashir, Iftikhar Ali, Zahid Nawaz proposed a systematic literature survey for various rainfall prediction techniques [4]. Sankhadeep Chatterjee, Bimal Datta, Soumya Sen, Nilanjan Dey use Hybrid Neural Network to predict the rainfall with the accuracy of 89.54% [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Time series data is the important aspects of modern research in the domain of knowledge discovery [4]. Spatial, temporal and spatio-temporal data is censorious for climate change and climate effect on the environment [5].…”
Section: Introductionmentioning
confidence: 99%